Assistants in nursing working with mental health consumers in the emergency department. (15th May 2018) - Gerace, Adam; Muir‐Cochrane, Eimear; O'Kane, Deb; Couzner, Leah; Palmer, Christine; Thornton, Karleen
Abstract: Nursing students, regardless of setting, require skills in working with people with mental health issues. One way to provide students with learning opportunities within the context of limited undergraduate mental health content and lack of mental health placements is through employment as assistants in nursing (AIN). The purpose of the study was to investigate the use of AINs employed in an emergency department in South Australia to supervise (continuous observation) mental health consumers on inpatient treatment orders. Twenty‐four participants took part in the study, with AINs ( n =  8, all studying in an undergraduate nursing programme), nurse managers ( n =  5), and nurses ( n =  11) participating in semi‐structured interviews. Data were analysed using thematic analysis. Themes focused on (i) the AIN role, their practice, boundaries or restrictions of their role, and the image consumers have of AINs; (ii) learning through experience, where the AIN role was a practical opportunity to learn and apply knowledge obtained through university studies; and (iii) support, which focused on how AINs worked with nursing staff as part of the healthcare team. Overall, participants believed that AINs played an important role in the ED in supervising consumers on involuntary mental health treatment orders, where their unique role was seen to facilitate more positive consumer experiences. The AIN role is one way for nursing students to develop skills in working with people with mental health issues.